The application of population data linkage to capture sibling health outcomes among children and young adults with neurodevelopmental conditions. A scoping review - Gray, Caitlin; Leonard, Helen; Cooper, Matthew N.; Rai, Dheeraj; Glasson, Emma J. (International Journal of Population Data Science, 2025)
Introduction Siblings of children with neurodevelopmental conditions have unique experiences and challenges related to their sibling role. Some develop mental health concerns as measured by self-reported surveys or parent report. Few data are available at the population level, owing to difficulties capturing wide-scale health data for siblings. Data linkage is a technique that can facilitate such research. Objective To explore the application of population data linkage as a research method to capture health outcomes of siblings of children with neurodevelopmental conditions. Inclusion criteria Peer reviewed papers that captured health outcomes for siblings of children and young adults with neurodevelopmental conditions using population data linkage. Methods JBI Scoping review methods were followed. Papers were searched within CINAHL, Ovid, Scopus, and Web of Science from 2000 to 2024 using search terms relating to `data linkage' `neurodevelopmental conditions' `siblings' and `health outcomes'. Results The final data extraction included 31 papers. The neurodevelopmental conditions of index children were autism, attention deficit hyperactivity disorder, intellectual disability, cerebral palsy and developmental delay. The mean follow-up time was 31 years, and the majority of studies originated from Scandinavia. Sibling health outcomes observed were psychiatric diagnoses, self-harm and suicide, other neurodevelopmental conditions, and medical conditions such as atopic disease, cancer and obesity. Conclusion Data linkage can help capture sibling health outcomes quickly across large cohorts with a range of neurodevelopmental conditions. Future research could be enhanced by focusing on siblings as the primary group of interest, increased integration of genealogical data, and comparisons between diagnostic groups and severity levels. Adoption of established rigorous reporting methods will increase the replicability of this type of research, and provide a stronger evidence-base from which to inform sibling supports.